Policy change and maintenance: policy entrepreneur in the anti-litterbugs campaign / Haijon Gunggut … [et al.] - Gunggut, Haijon; Zaaba, Zuraidah; Bagang, Tony Paridi; Ag Mohd Saufi, Dg. Siti Noor Saufidah (Faculty of Administrative Science and Policy Studies, 2012)
The Kota Kinabalu City Hall adopted the Anti litter Bugs Campaign program in 2008 as part of its going effort to promote a cleaner city. This is a departure from its previous Cleanliness Campaign program. The Cleanliness Campaign program focuses on cleanliness and therefore, did not address the actual cause. The Anti litter Bugs Campaign program on the other hand, focuses on the litterers, which is the primary cause of uncleanliness. The purpose of this paper is to account for the change and maintenance of the Anti litter Bugs Campaign program. It is argued that Kota Kinabalu City Hall learns from the failure of the previous campaign and as a result adopted a different approach. Although institution actors do learn, policy change does not necessarily ensue without the existence of policy entrepreneur. The change from Cleanliness Campaign program to Anti litter Bugs Campaign program in Kota Kinabalu City Hall highlighted the necessity for policy entrepreneur to come from upper management due to the top-down nature of the Malaysian policy-making process. Specifically, the observation, discussion, experience and reflection of the Director General of Kota Kinabalu City Hall at that time resulted in a program change proposal. This shows that both policy learning theory and policy entrepreneur concepts are necessary to account for the policy change in Kota Kinabalu City Hall in 2008. The implementation of the Anti litter Bugs Campaign program in the past 4 years (2008-2012) suggests the necessity of policy entrepreneur for policy maintenance. Thus, policy entrepreneur is a crucial factor in policy change and maintenance.